Employee Retention Factors in the Energy Sector in Klang Valley, Malaysia - Syarifah Mastura, Syed Abu Bakar; D'Cruz, Tulasi Amilia; Harpajan Singh, Tara Singh (INTI International University, 2018)
Employee retention is vital for organisations as it helps build competitive advantage and acts as a significant symbol of accomplished objectives. This paper aims at identifying the organisational commitment, rewards and compensations, and working environment which influences employee retention in the energy sector in Klang Valley, Malaysia. Prior studies have stated the importance of the relationship between the mentioned independent variables and employee retention. A quantitative study was conducted which consisted of 500 questionnaires distributed around the oil and gas companies in Malaysia. The independent variables of this study are organisational commitment, rewards and compensations, and working environment, whereas the dependant variable would be employee retention. The research results was analysed using Factor analysis, Multiple Regression Analysis and Reliability analysis by utilizing the SPSS statistic tool which will then be used for further discussion and to be related to the hypotheses and research questions. This analysis will allow in identifying if the independent variables would have a significant relationship with employee retention in the energy sector in Klang Valley, Malaysia.